Correlation between family support with work productivity of people with severe mental disorders (PSMD) in Bantur Community Health Center, Malang, Indonesia - Renny Nova; Heni Dwi Windarwati; Erik Meidianto (PAGEPress Publications, 2023)
Introduction: One impact on People With Mental Disorders (PSMD) is decreased productivity. As the closest people, families are expected to support PSMD to be productive in the community. Therefore, this study aimed to identify the correlation between family support and the work productivity of people with mental disorders. Design and Methods: This observational analytical study with a Cross-Sectional approach was conducted in the working area of the Bantur Community Health Center. Purposive sampling was used to obtain 107 samples. Data on family support were collected using a questionnaire and tested for validity, while the Endicott Work Productivity Scale (EWPS) questionnaire was used to measure PSMD work productivity. Results: The results showed a significant correlation between family support and PSMD work productivity, p = 0.028. The correlation was negative, meaning lower PSMD work productivity implied higher family support. Furthermore,emotional support was the most form of support provided by family members to PSMD. Work productivity is generally low, with PSMD work attitudes in the high category only in sub-variables. Conclusions: Family support is needed for people with mental disorders to be productive. Future studies should examine other factors that affect PSMD work productivity. Additionally, health services should innovate to create work programs that stimulate PSMD's potential and ability.